The effects of core-reflected waves on finite fault inversions with teleseismic body wave data - Qian, Yunyi (2018)
Teleseismic body waves are essential for imaging rupture processes of large earthquakes. Earthquake source parameters are usually characterized by waveform analyses such as finite fault inversions using only turning (direct) P and SH waves without considering the reflected phases from the core–mantle boundary (CMB). However, core-reflected waves such as ScS usually have amplitudes comparable to direct S waves due to the total reflection from the CMB and might interfere with the S waves used for inversion, especially at large epicentral distances for long duration earthquakes. In order to understand how core-reflected waves affect teleseismic body wave inversion results, we develop a procedure named Multitel3 to compute Green's functions that contain turning waves (direct P, pP, sP, direct S, sS and reverberations in the crust) and core-reflected waves (PcP, pPcP, sPcP, ScS, sScS and associated reflected phases from the CMB). This ray-based method can efficiently generate synthetic seismograms for turning and core-reflected waves independently, with the flexibility to take into account the 3-D Earth structure effect on the timing between these phases. The performance of this approach is assessed through a series of numerical inversion tests on synthetic waveforms of the 2008 Mw7.9 Wenchuan earthquake and the 2015 Mw7.8 Nepal earthquake. We also compare this improved method with the turning-wave only inversions and explore the stability of the new procedure when there are uncertainties in a priori information (such as fault geometry and epicentre location) or arrival time of core-reflected phases. Finally, a finite fault inversion of the 2005 Mw8.7 Nias–Simeulue earthquake is carried out using the improved Green's functions. Using enhanced Green's functions yields better inversion results as expected. While the finite source inversion with conventional P and SH waves is able to recover large-scale characteristics of the earthquake source, by adding PcP and ScS phases, the inverted slip model and moment rate function better match previous results incorporating field observations, geodetic and seismic data.